THE EFFECT OF APPLYING COLLABORATIVE STRATEGY READING (CSR)TOWARD STUDENTS’ READING COMPREHENSION AT THE EIGHTH GRADE OF MTs HUBBULWATHAN DURI - Riyawi, Mohd. Rafi (AL-ISHLAH: Jurnal Pendidikan, 2018)
The aim of this study is to find out the effectiveness of applying Collaborative Strategy Reading (CSR) on students’ reading comprehension. The research design was pre-experimental by giving pre-test and post-test to the class. It involved 36 participants of MTs Hubbulwathan Duri. Two research questions were posted in this study in order to find out the significant effect of using CSR on students’ reading comprehension. Pretest and posttest were administered in this study and paired sample t-test was used to analyze the data. The research finding shows that there was significant effect of using CSR on students’ reading comprehension. CSR contributed by 80,76 after giving post-test to the students with level of significant is 2.060. So, it can make inference that CSR can be applied in teaching reading comprehension especially at MTs Hubbulwathan Duri.Tujuan dari penelitian ini adalah untuk mengetahui keefektifan penerapan Collaborative Strategy Reading (CSR) pada pemahaman membaca siswa. Desain penelitian pra-eksperimental dilakukan dengan memberikan pre-test dan post-test ke kelas. Penelitian ini melibatkan 36 peserta MTs Hubbulwathan Duri. Dua pertanyaan penelitian dalam penelitian ini adalah untuk mengetahui pengaruh signifikan menggunakan CSR terhadap pemahaman membaca siswa. Pretest dan posttest diberikan dalam penelitian ini dan paired sample t-test digunakan untuk menganalisis data. Temuan penelitian menunjukkan bahwa ada pengaruh signifikan menggunakan CSR pada pemahaman membaca siswa. CSR yang disumbangkan oleh 80,76 setelah memberikan post-test kepada siswa dengan tingkat signifikan adalah 2,060. Jadi, dapat disimpulkan bahwa CSR dapat diterapkan dalam pengajaran membaca pemahaman terutama di MTs Hubbulwathan Duri